Visual Simulation of Modern Supply Chain Based on MR Virtual Reality Technology. (8th February 2022) - Yang, Jin
Abstract : In order to improve the management and operation efficiency of the modern supply chain, this paper combines the MR virtual reality technology to carry out the visual simulation of the modern supply chain. Moreover, this paper uses MR virtual simulation technology to perform intelligent perception of supply chain transportation equipment and transportation objects, recognize its shape and the force it receives, and ensure that there is no damage during the transportation process. The visual simulation of supply chain is realized by real-time dynamic display based on geometric model. Moreover, this paper combines the MR virtual reality technology to define the geometric and kinematic characteristics of the modeled object, then encapsulates these characteristics into the object class, and defines the behavior characteristics to establish an object class library. Finally, the experimental research verifies that the modern supply chain visual simulation technology based on MR virtual reality technology has a good simulation effect in the supply chain system.